Edukasi Nifas pada Masa Pandemi Covid 19 di Puskesmas Koni Kota Jambi - Ratu Kusuma (Jurnal Abdimas Kesehatan (JAK), 2023)
Postpartum maternal services are health services provided to postpartum mothers (40 days postpartum) according to standards, at least 3 times according to schedule, namely KF1 (6-3 days after delivery), KF2 (4-28 days after delivery), and KF3 (29-42 days after delivery). Its success is measured by the coverage of KF3 (national target: at least 90%). This service activity was carried out at the Puskesmas Koni in Jambi City, where KF3 coverage had reached 100% of 268 postpartum women in 2020. Based on the identification of the problem, there were 5 problems related to postpartum mothers, namely: 1) the provision of information for postpartum mothers was not maximal at the KIA Polyclinic; 2) low knowledge of mothers about the postpartum period and postpartum services; 3) there are still negative attitudes of mothers and families about the postpartum period; 4) the low number of postpartum visits, especially during the Covid 19 pandemic; and 5) the low participation of mothers in participating in health education at Posyandu activities for toddlers. One of the efforts to overcome these problems is the provision of education in the form of group education. The aim is to increase knowledge of mothers and families about the postpartum period and postpartum services, change attitudes and take healthy actions related to the postpartum period. This series of activities has been carried out since March-July 2021, while education was given on July 13, 2021 for 5 postpartum mothers who were accompanied by their families. This group education is given 1 meeting for 50-60 minutes; using flipcharts and booklets. Identification of mother's knowledge and attitudes (pre and post-education) using the same questionnaire sheet. The results obtained are an increase in the average knowledge of 3.8 and an increase in the average attitude of 4.3 after being given education.